THE PRINCIPLE OF EQUIVALENCE OF ENERGY SPENT ON PROCESS AND OF STEP OF TIME - Veitsman, Emil V. (International Journal of Research -GRANTHAALAYAH, 2021)
It was formulated the physical principle of the equivalence of the energy expense during the process of the Universe spreading and of the step of time. It was also shown that physical time is a material quantity connected with expending our Universe at constant velocity. A parallel was carried out between the increase of the size of the drops and bubbles and the expending of the Universe. The above principle is in full agreement with SR and GTR. It was shown as well that physical time could quantize.